Nomenclatura de variedades de frijol común liberadas en Centroamérica y el Caribe - Rosas Sotomayor, Juan Carlos; Beaver, James S.; Beebe, Stephen E.; Viana Ruano, A (2004)
Nomenclature of common bean varieties released in Central America and the Caribbean. Several improved common bean varieties have been released in different countries of Central America and the Caribbean in recent years. National bean programs and other organizations involved in variety release processes have designated the same varieties with different names. In the short term, this situation can cause confusion in the identification of the improved bean varieties currently utilized by farmers. The purpose of this document is to serve as a reference for researchers, farmers, seed distribution agents, government officials and traders, in making decisions regarding the use of these improved varieties for commercial production of grain or seed, industrial processing and marketing in the region.